The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0961203317725589
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of patients with systemic lupus erythematosus who meet the diagnostic criteria for TAFRO syndrome

Abstract: Purpose TAFRO syndrome is a novel disorder manifesting as fever, anasarca, thrombocytopenia, renal insufficiency and organomegaly, and its etiology has not been clarified. The aim of this study was to elucidate similarities and differences between systemic lupus erythematosus (SLE) and TAFRO syndrome. Methods We examined 46 consecutive patients diagnosed with SLE and determined whether they meet the proposed diagnostic criteria for TAFRO syndrome (2015 version). Results Of the 46 patients with SLE, four (8.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These findings highlight that existing iMCD-TAFRO case reports might include patients with undiagnosed autoimmune disorders as suggested previously. [32][33][34][35][36] Thus, clinicians need to carefully exclude those disorders, and the diagnostic criteria need to be defined to avoid misdiagnosis of autoimmune disorders as iMCD-TAFRO.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight that existing iMCD-TAFRO case reports might include patients with undiagnosed autoimmune disorders as suggested previously. [32][33][34][35][36] Thus, clinicians need to carefully exclude those disorders, and the diagnostic criteria need to be defined to avoid misdiagnosis of autoimmune disorders as iMCD-TAFRO.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that systemic lupus erythematosus (SLE) sometimes manifests the same characteristics as TAFRO syndrome. Hasegawa et al examined patients with SLE who met the criteria for TAFRO syndrome and found that older patients with SLE (onset ≥ 50 years of age) had clinical features similar to those of TAFRO syndrome [32]. Although anti-SS-A antibody was positive and IgG4 was elevated in the present case, the patient did not meet the criteria for either SjS or IgG4-related disease.…”
Section: Discussionmentioning
confidence: 56%
“…TAFRO syndrome has similar clinical and histopathological characteristics to those of many autoimmune diseases. Approximately 50% of patients often have autoimmune dysfunction 37–39 . For example, rheumatoid‐associated antibodies, platelet‐associated immunoglobulin antibodies, anti‐thyroid antibodies, anti‐Sjögren's syndrome A (anti‐SSA) antibodies, and anti‐SSB antibodies are common immune‐related antibodies in TAFRO syndrome.…”
Section: Etiologymentioning
confidence: 99%